1988
DOI: 10.1177/001872678804100501
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Methodological Problems Within Occupational Stress and Burnout Research

Abstract: This article examines the implicit assumptions underlying current research into occupational stress and burnout. It argues that the two fields utilize similar theoretical models and research techniques and therefore have a number of problems in common. These problems arise from their common tendency to adopt a psychological perspective which pays insufficient attention to the complexity of the interrelationship between social conditions and subjective experience. The article suggests that both fields could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
5

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(39 citation statements)
references
References 29 publications
0
34
0
5
Order By: Relevance
“…The importance of longitudinal data in the study of stress has been noted in the literature (e.g., Handy 1988;Lazarus 1991). Longitudinal data allows a clearer understanding of the causal order of the variables, and of the processes taking place over time.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of longitudinal data in the study of stress has been noted in the literature (e.g., Handy 1988;Lazarus 1991). Longitudinal data allows a clearer understanding of the causal order of the variables, and of the processes taking place over time.…”
Section: Discussionmentioning
confidence: 99%
“…Meyerson (1994) and Handy (1988Handy ( , 1991 showed that stress occurs in a particular context, since individuals differ in the meaning they attribute to stressful experiences. The influence of social construction of stressful experiences should also be taken into account.…”
mentioning
confidence: 99%
“…En ce qui concerne les méthodes utilisées, il peut être dit que même si de rares études réalisées sous le paradigme du stress donnent une place à la question du sens et si quelques chercheurs rattachés à ce courant réclament davantage de recherches qualitatives (Bourbonnais et al, 2000 ;Handy, 1988), les études sur le stress font principalement appel à des méthodes quantitatives. L'évaluation du stress passe ainsi habituellement par la technique de mesure de paramètres physiologiques et par des enquêtes administrées sous forme de questionnaires le plus souvent auto-évalués individuellement.…”
Section: Les Divergences Entre Les Approchesunclassified